Non-coding RNAs as Regulators of Cellular Senescence in Idiopathic Pulmonary Fibrosis and Chronic Obstructive Pulmonary Disease - Omote, Norihito; Sauler, Maor (Frontiers in Medicine, 2020)
Cellular senescence is a cell fate implicated in the pathogenesis of Idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD). Cellular senescence occurs in response to cellular stressors such as oxidative stress, DNA damage, telomere shortening, and mitochondrial dysfunction. Whether these stresses induce cellular senescence or an alternative cell fate depends on the magnitude of cellular stress and intrinsic factors that regulate the cellular stress response. Non-coding RNAs, including both microRNAs and large non-coding RNAs, are key regulators of cellular stress responses and cellular senescence. In this review, we will discuss cellular mechanisms that contribute to senescence in IPF and COPD and highlight recent advances in our understanding of how these processes are influenced and regulated by non-coding RNAs. We will also discuss the potential therapeutic role for targeting non-coding RNAs to treat these chronic lung diseases.